Penentuan Koefisien Hidraulik pada Tapak NSD, Serpong, Berdasarkan Metoda Uji Permeabilitas In-Situ - Syaeful, Heri; Sucipta, Sucipta (EKSPLORIUM, 2013)
Inline with the increase of amount of radioactive waste, PTLR-BATAN plans to build the Near Surface Disposal (NSD) facility, especially in the preliminary stages is the Demo Plant of NSD facility. NSD is a low to medium level radioactive waste storage concept. Most important aspect in the site study for planning NSD is hydrogeological aspect especially related to the migration of radionuclides to the environment. In the study of radionuclide migration, a preliminary parameter which is required to know is the hydraulic conductivity in order to deliver the soil and rock hydraulic conductivity values ​​in the site then conducted the in-situ permeability test. Based on the test, obtained soil and rock hydraulic conductivity values​ranging from 10-6 to 10-2 cm/sec. The greatest hydraulic conductivity value located in the gravelly silt soil units which is in the site, constitute as aquifer, with depth ranging from 8-24 m, with hydraulic conductivity value ​​reached 10-2 cm/sec.